Framing Kegagalan Pemerintah Pada Media Sosial Partai Keadilan Sejahtera Jelang Pemilu 2024 - Febrianti, Diani; Saptawan, Eddi Kurnianto (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The 2024 Indonesian election campaign time has not officially started, but the fight for public sympathy and votes has already begun long before it. Candidates and Parties, already busy performing, either positive publicity for themselves, or negative campaign for the opposing party. This research aims to observe framing strategies that already appear on social media, ahead of the 2024 elections. The topic chosen was the framing of government failure, with the social media studied is the Instagram account of the Keadilan Sejahtera Party (PKS), which can be considered the government's opposition party. The data that will be discussed is content in June to July 2023 which is considered relevant enough to show PKS's political communication ahead of the 2024 elections. This article uses a descriptive qualitative research methodology with Entman model framing analysis. The focus of the research is problem identification, causal interpretation, moral evaluation, treatment recommendation, which appear in the Instagram content. The research conclusion states that there is indeed a framing of state failure in the content studied. PKS carried out framing which essentially explained that the government did not side with its citizens, and the government betrayed the community's mandate. This framing was also accompanied by strengthening the PKS political brand; “PKS is always with the People”.